2021
DOI: 10.3390/horticulturae7040077
|View full text |Cite
|
Sign up to set email alerts
|

‘Hass’ Avocado Internal Disorders under Simulated Export Conditions and Its Relationship with Flesh Mineral Content and Preharvest Variables

Abstract: The most important issues that affect consumer fruit acceptance in the ‘Hass’ avocado international market are flesh disorders. These defects can be influenced by both pre- and postharvest factors. The aim of this work was to evaluate the effect of the harvest season, storage time, mineral content, and preharvest variables on internal fruit disorders. Here, fruit was sampled from four farms in Antioquia (Colombia) at 22%, 26%, and 30% dry matter (DM) content. Samples were stored and ripened under simulated exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The Ca contained in the fruit is accumulated during the first five months of development, because it moves towards the actively growing cells (Salvo, 2017), it may explain why Ca concentrations were lower from fruit measuring 65 to 70 mm until the beginning of harvest. Escobar et al (2021) found high content of calcium in fruits associated to reduced avocado flesh disorders and improved the internal fruit quality.…”
Section: Calcium Nutritional Dynamicsmentioning
confidence: 90%
“…The Ca contained in the fruit is accumulated during the first five months of development, because it moves towards the actively growing cells (Salvo, 2017), it may explain why Ca concentrations were lower from fruit measuring 65 to 70 mm until the beginning of harvest. Escobar et al (2021) found high content of calcium in fruits associated to reduced avocado flesh disorders and improved the internal fruit quality.…”
Section: Calcium Nutritional Dynamicsmentioning
confidence: 90%
“…The postharvest quality affects consumer perceptions when purchasing or repurchasing avocado fruit [77]. High boron concentrations in the flesh can reduce the incidences of flesh discoloration, vascular browning and body rot [25]. Furthermore, boron provides health benefits such as improving bone formation and maintenance, facilitating insulin action, increasing glucose metabolism and alleviating arthritis symptoms [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…Agronomy 2022, 12, 1479 2 of 15 Nutrient allocation within the tree during the later stages of fruit development also affects the quality of mature fruit, as the levels of nutrients such as boron, calcium, magnesium and nitrogen can influence the size, taste and postharvest quality of fruit [6,18,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis was performed following the procedure published by Escobar et al [20]. Briefly, the flesh was dried at 70 • C in a forced convection oven (Memmert UF 110) until a constant weight was attained.…”
mentioning
confidence: 99%